Aggressive and acute periodontal diseases. (June 2014) - Albandar, Jasim M.
Abstract: Inflammatory periodontal diseases are highly prevalent, although most of these diseases develop and progress slowly, often unnoticed by the affected individual. However, a subgroup of these diseases include aggressive and acute forms that have a relatively low prevalence but show a rapid‐course, high rate of progression leading to severe destruction of the periodontal tissues, or cause systemic symptoms that often require urgent attention from healthcare providers. Aggressive periodontitis is an early‐onset, destructive disease that shows a high rate of periodontal progression and distinctive clinical features. A contemporary case definition of this disease is presented. Population studies show that the disease is more prevalent in certain geographic regions and ethnic groups. Aggressive periodontitis is an infectious disease, and recent data show that in affected subjects the subgingival microbiota is composed of a mixed microbial infection, with a wide heterogeneity in the types and proportions of microorganisms recovered. Furthermore, there are significant differences in the microbiota of the disease among different geographic regions and ethnicities. There is also evidence that the Aggregatibacter actinomycetemycomitans ‐JP2 clone may play an important role in the development of the disease in certain populations. The host response plays an important role in the susceptibility to aggressive periodontitis, where the immune response may be complex and involve multiple mechanisms. Also, genetic factors seem to play an important role in the pathogenesis of this disease, but the mechanisms of increased susceptibility are complex and not yet fully understood. The available data suggest that aggressive periodontitis is caused by mutations either in a few major genes or in multiple small‐effect genes, and there is also evidence of gene–gene and gene–environment interaction effects. Diagnostic methods for this disease, based on a specific microbiologic, immunologic or genetic profile, currently do not exist. Genetic markers have the potential to be implemented as screening tools to identify subjects at risk. This approach may significantly enhance treatment outcome through the early detection and treatment of affected subjects, as well as using future approaches based on gene therapy. At present, the treatment of this disease is directed toward elimination of the subgingival bacterial load and other local risk factors. Adjunctive use of appropriate systemic antibiotics is recommended and may contribute to a longer suppression of the microbial infection. Other aggressive forms of periodontal diseases occur in patients who are affected with certain systemic diseases, including the leukocyte adhesion deficiency syndrome, Papillon–Lefèvre syndrome, Chediak–Higashi syndrome and Down syndrome. Management of the periodontal component of these diseases is very challenging. Acute gingival and periodontal lesions include a group of disorders that range from nondestructive to destructive forms, and these lesions are usually associated with pain and are a common reason for emergency dental consultations. Some of these lesions may cause a rapid and severe destruction of the periodontal tissues and loss of teeth. Oral infections, particularly acute infections, can spread to extra‐oral sites and cause serious medical complications, and even death. Hence, prompt diagnosis and treatment are paramount.